Design and Development of Virtual Reality Media on Computer System Learning to Enhance Students' Cognitive Abilities - Wahyudin; Akbar, Anthonio; Nugraha, Eki; Riza, Lala Septem; Nazir, Shah (Universitas Pendidikan Ganesha, 2025)
The quality of education in Indonesia remains a significant concern, as reflected in the PISA survey, which ranks Indonesia 72nd out of 77 participating countries. One contributing factor is the limited development of Higher Order Thinking Skills (HOTS) among students, particularly in cognitive, psychomotor, and affective domains. This study aims to design and develop Virtual Reality (VR) media integrated with a Self-Directed Learning (SDL) model to enhance students' cognitive abilities in computer system learning. Employing a Research and Development (R&D) approach with the ADDIE model, this experimental research involved 33 students and applied a One Group Pre-test Post-test design. Data were collected through cognitive tests and student response questionnaires, and analyzed using paired sample t-tests and N-Gain calculations. The results indicated a significant improvement in students' cognitive abilities, with overall conceptual gains categorized as moderate and positive student responses toward the VR media. These findings suggest that SDL-based VR media can effectively foster students’ cognitive development, encourage active, independent learning, and serve as an innovative instructional solution to address educational quality challenges. The study implies that immersive technology integration, when paired with appropriate learning models, holds substantial potential in enhancing students' higher-order thinking skills in the digital era.